2011
DOI: 10.1088/2040-8978/13/7/075702
|View full text |Cite
|
Sign up to set email alerts
|

Tight focusing of partially coherent, partially polarized vortex beams

Abstract: We study the tight focusing properties of partially coherent, partially polarized vortex beams through a high numerical aperture (NA) objective. The influence of the degree of polarization, the topological charge, the correlation length of the incident beam, and the NA of the objective on the intensity in the focal region is investigated in great detail. We also perform a study on the degree of coherence around the focal plane. We found that the intensity distribution and the degree of coherence in the focal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In recent years, tight focusing of radially and azimuthally polarized light beams through a high numerical aperture (NA) objective lens has attracted intensive attention and extensive investigation, because of their fascinating features and wide potential applications [1][2][3][4][5][6][7][8][9][10]. It is found that, when radial polarizations are highly focused, a very strong longitudinal electric field component will emerge in the focal region, which forms an extremely tight focal spot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, tight focusing of radially and azimuthally polarized light beams through a high numerical aperture (NA) objective lens has attracted intensive attention and extensive investigation, because of their fascinating features and wide potential applications [1][2][3][4][5][6][7][8][9][10]. It is found that, when radial polarizations are highly focused, a very strong longitudinal electric field component will emerge in the focal region, which forms an extremely tight focal spot.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a tight focal spot is of great help to improve the resolution of microscopy [11,12], enhance laser cutting ability in material processing [13], and can also be applied to improve the performance of optical tweezers due to the reduction of scattering [10,14,15]. Tight focusing of the electromagnetic field with various polarizations have been investigated, such as the linearly polarized, circularly polarized, radially polarized, azimuthally polarized, and hybridly polarized beams, as well as vortex beams [1][2][3][4][5][6][7]. It is also revealed in the vicinity of the focus that, for linear incident polarization, the generated longitudinal polarized component is not rotationally symmetric, which causes an asymmetric deformation of the focal spot [16,17]; for radial polarization input, it generates a strong longitudinal electric field component in the focal zone [11,18]; In contrast, the azimuthal incident polarization produces a strong magnetic field on the optical axis [19], meanwhile the electric field is purely transverse and null at the center [2].…”
Section: Introductionmentioning
confidence: 99%